Revisão sistemática aplicada à determinação de resíduos de agrotóxicos em alimentos: técnicas de análise e práticas de validação intralaboratorial - Roberto Cesar Santos de Sousa (2018)
A systematic review was proposed to answer the question: The methods validated for the study of pesticides residues in food follow the recommendations of guidelines for single-laboratory validation of analytical methods? Two analysts selected articles about method validation for the analysis of pesticide residues in foods published after 2002, year of publication of the harmonized guideline for the single-laboratory validation by IUPAC/ISO/AOAC. The searches were conducted at the main databases online (AGRIS, Cochrane Library, FSTA, LILACS, MEDLINE/PubMED, SciELO and Web of Science), at the BDTD for thesis and dissertation, at the OpenGrey database to fill the gray literature, in addition to manual searches in the references of the selected studies. 1809 articles were found, resulting in 835 articles after the selection stages. Altogether, 868 quantitative methods and 24 qualitative methods were disclosed among the recovered articles. The results obtained for the quantitative methods showed that the study of the performance parameters was influenced, mainly, by own factors of the laboratories, being attributed to the validation guidelines the evidenced behavior for the matrix effects and robustness. Classical parameters such as trueness, precision under repeatability conditions and selectivity reached frequencies of 97,58%; 97,06% and 94,66%, respectively. On the other hand, the parameters uncertainty of measurement and robustness presented frequencies of 8,91% and 4,92%, respectively. For qualitative methods, it was observed that the validation guides were incongruent about the parameters that should be studied, which probably influenced the evidenced profile of the studied parameters. The classical parameters of sensitivity, selectivity and limit of detection were analyzed with frequencies of 91,67%, 70,83% and 91,67%, respectively. Again, the uncertainty (associated with the unreliability region) and robustness were the less frequent parameters along with the intermediate precision (concordance). It was understood that there are aspects regarding the method validation within the area of residues of pesticides in food that need to be solved so that the works will be more cohesive and harmonized. This will allow the scientific community a better understanding about the performance of current technologies in the field of food analysis, identifying the most promising and efficient techniques for the analysis of pesticides through systematized procedures.